The Effects on Absorbed Dose Distribution in Intraoral X-ray Imaging When Using Tube Voltages of 60 and 70 kV for Bitewing Imaging - Kristina Hellén-Halme; Mats Nilsson (Stilus Optimus, 2013)
Objectives: Efforts are made in radiographic examinations to obtain the best image quality with the lowest possible absorbed dose to the patient. In dental radiography, the absorbed dose to patients is very low, but exposures are relatively frequent. It has been suggested that frequent low-dose exposures can pose a risk for development of future cancer. It has previously been reported that there was no significant difference in the diagnostic accuracy of approximal carious lesions in radiographs obtained using tube voltages of 60 and 70 kV. The aim of this study was, therefore, to evaluate the patient dose resulting from exposures at these tube voltages to obtain intraoral bitewing radiographs.Material and Methods: The absorbed dose distributions resulting from two bitewing exposures were measured at tube voltages of 60 and 70 kV using Gafchromic® film and an anatomical head phantom. The dose was measured in the occlusal plane, and ± 50 mm cranially and caudally to evaluate the amount of scattered radiation. The same entrance dose to the phantom was used. The absorbed dose was expressed as the ratio of the maximal doses, the mean doses and the integral doses at tube voltages of 70 and 60 kV.Results: The patient receives approximately 40 - 50% higher (mean and integral) absorbed dose when a tube voltage of 70 kV is used.Conclusions: The results of this study clearly indicate that 60 kV should be used for dental intraoral radiographic examinations for approximal caries detection.